Tower, U.S. Pavilion and Northwest Orient (Seville Enterprises, Inc.)
On the Spokane River, the Great Northern Clock Tower, Japan and U.S. Pavilions, and Northwest Orient Chinese Junk are shown across from the Washington State Pavilion.